Analyzed New Design Data Driven Modelling of Piezoelectric Power Generating System - Solly Aryza; Zulkarnain Lubis; M. Isa Indrawan; Syahril Efendi; Poltak Sihombing (Budapest International Research and Critics University, 2021)
The piezoelectric speed bumps designed in this study consist of a speed bump mechanical system that functions to receive input from motorized vehicle pressure, piezoelectric cantilever system as a component producing electrical energy and energy harvesting system as energy harvester from piezoelectric material. One system module consists of a piezoelectric parallel circuit connected to the MB39C811 buck converter. In this paper, we will discuss the mechanism for analyzing the design and modeling of a piezoelectric power plant system on a bluff body-based speed bump with a cantilever system for variations in motor vehicle speed by means of physical modeling. In the piezoelectric speed bump in the form of a bluff body, it can be seen that the air flow when passing through the triangular cross section has an increase in speed so that the resulting vortex has a high speed. This is what causes high vibrations in the piezoelectric so that the maximum voltage and the average voltage are the highest. Piezoelectric speed bumps are capable of generating electrical power with an input of 60 times the motorized vehicle track of 2.166mWh with an efficiency of 2.87% compared to manual input.